Analysis of the Effectiveness of Loyalty Membership Programs in Increasing Customer Retention Using Net Promoter Score (NPS) with Information System Support - Virdies Nur C Cahya; Refius Setyanto; Paradise Paradise (Eduvest - Journal of Universal Studies, 2025)
This study analyzes the effectiveness of membership loyalty programs in increasing customer retention using Net Promoter Score (NPS) with the support of information systems. Loyalty programs are one of the effective strategies in maintaining long-term relationships with customers. However, its success relies heavily on the right measurement of customer satisfaction, one of which is through NPS. NPS provides clear insights into customer loyalty levels by distinguishing between "promoters" and "detractors". Information systems play an important role in supporting the collection and analysis of customer data in real-time, enabling companies to create more personalized and relevant offers. Through the Systematic Literature Review (SLR) approach, this study reviewed various literature related to the implementation of loyalty programs, NPS measurement, and the role of information systems in improving customer retention. The results show that a combination of relevant loyalty programs, effective NPS measurement, and supportive information systems can create a better customer experience, increase satisfaction, and strengthen customer loyalty. This research also provides recommendations for companies in optimizing the use of information technology and periodic evaluation of loyalty programs to achieve maximum results in customer retention.